Effects of the kidding season and sex on the growth and legtissue composition of kid goats of the Murciano-Granadina breed under natural lactation - Sanz Toro B.; Lozano López J.; Sanz Sampelayo M.R. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
With the goal of establishing a Quality Assurance System and thus enabling the obtention of a Quality Certificate for goat-kid carcasses of the Murciano-Granadina breed, a series of experiments was carried out in which the animals were fed by their dams under a natural regime. The aim of the experiments was to determine, on the one hand, the characteristics of the composition of the animal carcass that determine its quality and, on the other, the possible effects produced on the growth and development of animals by the implicated factors. An analysis was made of the possible effects of the kidding season (autumn vs spring) and of the sex of the kid goats on growth rate (g/day), in an experimental group of 36 kidgoats (18 per season, 9 male and 9 female). All the animals were fed by their dams until they attained the size at which they would be killed (8±1kg), after which the effects of the above factors on the tissue composition and intramuscular fat content of the leg were analysed. The conclusions drawn from the results obtained are that the animals, in general, presented good growth and development with better results produced by the animals reared in the autumn. Nevertheless, and taking into account the factors involved, the amount of the body fat depended on the type of fat deposit in question.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)